De Gustibus and Disputes about Reference Dependence - Campos-Mercade, Pol; Goette, Lorenz; Graeber, Thomas; Kellogg, Alexandre; Sprenger, Charles (Review of Economic Studies, 2026)
Existing tests of reference-dependent preferences assume universal loss aversion. This paper examines the implications of heterogeneity in gain-loss attitudes for such tests. In experiments on labour supply and exchange behaviour, we first measure gain-loss attitudes and then study a canonical treatment effect that distinguishes different models of reference dependence. We document substantial heterogeneity in gain-loss attitudes and evidence against universal loss aversion. Moreover, we find heterogeneous treatment effects over gain-loss attitudes consistent with formulations of expectations-based reference points. Assuming homogeneous preferences would lead to different and potentially incorrect conclusions in these tests. Our findings provide foundational support for reference points derived from expectations and help reconcile inconsistencies in prior empirical exercises.